Development of Science Modules Based on a Culturally Responsive Teaching Approach on Banten's Typical Pottery Crafts to Scientific Literacy - Dinda Wulandari Hermina Putri; Siti Romlah Noerhodijah; Ratu Bai Rohimah; Trian Pamungkas Alamsyah (ISER (Indonesian Science Education Research), 2026)
This study was conducted based on field observations showing a lack of fundamental science literacy skills and limited teaching materials to support them. Therefore, a science module based on a culturally responsive teaching (CRT) approach was developed utilizing Banten's traditional pottery craft to facilitate the scientific literacy of seventh-grade students. This study aimed to analyze the validity of the CRT-based science module for improving scientific literacy. The research and development (R&D) method was employed using the ADDIE development model, which was limited to three stages: analysis, design, and development. Data were collected through validation questionnaires using instruments for expert validation. Nine validators, comprising subject matter experts, teaching material experts, and practitioner experts, conducted the validation. The obtained data were analyzed using quantitative and qualitative methods. The results showed that the science module was classified as "very feasible" with a percentage of 89.23%, with details of 87.95% for subject matter experts, 93.16% for teaching material experts, and 86.58% for science practitioners. It can be concluded that the science module based on a culturally responsive teaching (CRT) approach, which was developed using Banten's traditional pottery craft to facilitate the science literacy of seventh-grade students are appropriate for use in learning activities.